2005
DOI: 10.1016/j.pbb.2004.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clomipramine on self-control choice in Lewis and Fischer 344 rats

Abstract: Rates of delay discounting (impulsive choice) have been shown to vary among individuals, particularly people who abuse drugs relative to those who do not, but factors that may contribute to these differences have not been identified. To explore a role for possible genetic and neurochemical determinants, Lewis (n=8) and Fischer 344 (n=8) rats were allowed to choose between one food pellet delivered immediately and three food pellets delivered after increasing delays. The delays to the large reinforcer (0, 10, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
118
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(146 citation statements)
references
References 48 publications
24
118
4
Order By: Relevance
“…We found that RHA-I rats made fewer choices of a large reward when the delay was increased from 0 to 20 and 40 s. Thus, RHA-I rats prefer an immediate reward and show marked choice impulsivity compared with RLA-I rats. Other studies have found strain differences in impulsivity with the same approach, such as greater impulsivity in Lewis rats compared with Fischer 344 rats (Anderson and Woolverton, 2005). This finding appears to agree with the increased susceptibility to addiction (and effects of addictive drugs) of Lewis vs Fischer 344 rats (Kosten and Ambrosio, 2002, for review;Sánchez-Cardoso et al, 2009) and is also in line with similar findings in RHA vs RLA rats (eg, Fattore et al, 2009;Fernández-Teruel et al, 2002a) and the current results.…”
Section: Increased Adjunctive Drinking Acquisition In Rha-i Ratsmentioning
confidence: 88%
“…We found that RHA-I rats made fewer choices of a large reward when the delay was increased from 0 to 20 and 40 s. Thus, RHA-I rats prefer an immediate reward and show marked choice impulsivity compared with RLA-I rats. Other studies have found strain differences in impulsivity with the same approach, such as greater impulsivity in Lewis rats compared with Fischer 344 rats (Anderson and Woolverton, 2005). This finding appears to agree with the increased susceptibility to addiction (and effects of addictive drugs) of Lewis vs Fischer 344 rats (Kosten and Ambrosio, 2002, for review;Sánchez-Cardoso et al, 2009) and is also in line with similar findings in RHA vs RLA rats (eg, Fattore et al, 2009;Fernández-Teruel et al, 2002a) and the current results.…”
Section: Increased Adjunctive Drinking Acquisition In Rha-i Ratsmentioning
confidence: 88%
“…The relationship between impulsivity and drug abuse vulnerability is known to involve genetic factors, as Lewis rats and rats that have been selectively bred for high saccharin intake (HiS) show both enhanced vulnerability to drug abuse and increased impulsive choice compared to Fischer 344 [2,44,50,83] and rats selectively bred for low saccharin intake (LoS) [14,22,63,64]. The present findings, combined with previous findings showing that IC rats are more vulnerable to drug abuse than EC rats [7,32,82], indicate that environmental factors also influence both impulsivity and drug abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is known that genetic factors play a role in the relationship between impulsivity and drug abuse vulnerability [2,14], environmental factors also play a role [54]. Rats reared in an enriched condition (EC) with novel objects and social cohorts self-administer less amphetamine than rats reared in an isolated condition (IC), without objects or social cohorts [7,32,82].…”
Section: Introductionmentioning
confidence: 99%
“…Impulsivity is related to drug addiction by studies reporting that rats that are intolerant of reward delay subsequently acquire cocaine self-administration more rapidly and at lower doses (Perry et al, 2005) and also self-administer more alcohol (Poulos et al, 1995(Poulos et al, , 1998 than do delaytolerant rats (for review, see Olmstead, 2006). In addition, Lewis rats, as compared to Fischer rats, exhibit more intolerance to reward delay (Anderson and Woolverton, 2005) and more readily self-administer drugs of abuse, including cocaine (Kosten et al, 1997;Haile and Kosten, 2001), morphine (Ambrosio et al, 1995;Martin et al, 1999), and alcohol (Suzuki et al, 1988). In humans, the trait of impulsivity has been proposed to predispose vulnerability to drug abuse (Zuckerman, 1993;Jentsch and Taylor, 1999;Svrakic et al, 1999;Volkow and Fowler, 2000;Kreek et al, 2005) and there is evidence that impulsivity, as measured by selfreports in humans, is higher in alcohol-dependent patients (Patton, et al, 1995;Chen et al, 2007), and in drug abusers (Allen et al, 1998;Fillmore and Rush, 2002), while recent evidence implicates impulsivity is an important feature of early-onset alcoholism (Dom et al, 2006a, b).…”
Section: Vulnerability To Impulsivitymentioning
confidence: 99%
“…For example, Lewis rats exhibit more intolerance to reward delay than Fischer rats (Anderson and Woolverton, 2005), and Lewis rats also exhibit more rapid acquisition and higher asymptotic levels of sign-tracking CR performance than Fischer rats (Kearns et al, 2006). Intolerance to reward delay or delay discounting is one of several indices of impulsivity, and there is evidence that sign-tracking resembles impulsive responding on other behavioral tasks as well (Monterrosso and Ainslie, 1999).…”
Section: Vulnerability To Impulsivitymentioning
confidence: 99%